2014
DOI: 10.7603/s40601-013-0020-2
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Education Environment and Open Data Initiative:Steps towards User-Powered Society-Oriented Systems

Abstract: The economy is not keeping pace with the increasing speed of technological evolution. The inadequacy of the current system of education is a possible reason for this. Evolution forces us to produce experts for tasks and businesses which do not yet exist, to teach them technologies which have not yet been devised. The best way to produce experts is to accentuate the learner's best abilities and skills, assess the learner's potential and develop it further. We badly need revolutionary methods to facilitate intel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…Such artefacts (e.g heuristics, frameworks, or templates) can be easily shared by the PKMS community members or expertly developed by WHOMER professionals. The PKMS Educational Learning Assets Agenda for Personal Learning Environments (PLEs): Irrespective of the remedies put forward in this article, Digital Personal Learning conceptualizations are gaining momentum aiming for designing motivational content and enabling interventions and for the further and faster (self-)development of learners’ potentials [ 45 , 46 ]. As an example of digital platform ecosystems (DPE), collaborating learning management systems (LMS) and knowledge management systems (KMS) are meant, in this respect, to accommodate social actors with highly diverse ambitions and skills as well as expectations to gainfully utilize the DPEs’ resources and generative potential in their personal and local contexts [ 47 ].…”
Section: The Negentropic Consequences Of the Value-adding World:3bmentioning
confidence: 99%
“…Such artefacts (e.g heuristics, frameworks, or templates) can be easily shared by the PKMS community members or expertly developed by WHOMER professionals. The PKMS Educational Learning Assets Agenda for Personal Learning Environments (PLEs): Irrespective of the remedies put forward in this article, Digital Personal Learning conceptualizations are gaining momentum aiming for designing motivational content and enabling interventions and for the further and faster (self-)development of learners’ potentials [ 45 , 46 ]. As an example of digital platform ecosystems (DPE), collaborating learning management systems (LMS) and knowledge management systems (KMS) are meant, in this respect, to accommodate social actors with highly diverse ambitions and skills as well as expectations to gainfully utilize the DPEs’ resources and generative potential in their personal and local contexts [ 47 ].…”
Section: The Negentropic Consequences Of the Value-adding World:3bmentioning
confidence: 99%
“…That is why we badly need revolutionary methods to facilitate intelligent personalization of study processes and approaches to make innovative education content more attractive and motivational for the learner (Khriyenko and Khriyenko, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Educational activities are nowadays happening in open and networked learning environments, characterized by increasing complexity and fast-paced change (Chatti et al, 2017). The increasing availability of OER, MOOC and other open data sources provides challenges for stakeholders to get more from these data (Atenas, Havemann, & Priego, 2015;Colpaert, 2018;Khriyenko & Khriyenko, 2013;Zuiderwijk, Janssen, & Davis, 2014). Verbert, Manouselis, Drachsler, and Duval (2012) reported that the availability of open data sets is considered as key for research and application purposes.…”
Section: Open Data For Education and Interlinking Educational Datamentioning
confidence: 99%
“…The whole education sector is facing increasing amounts of data available, but lack to utilize such opportunities for working with them (Cervone, 2016;Huda et al, 2017;Máchová, Komárková, & Lněnička, 2016;Picciano, 2012;Vieira, Parsons, & Byrd, 2018). New tools and techniques for storing, managing, processing, analysing, visualization, and sharing of these data fast and easily are available for everyone (Aghabozorgi, Mahroeian, Dutt, Wah, & Herawan, 2014;Khriyenko & Khriyenko, 2013;Klašnja-Milićević, Ivanović, & Budimac, 2017). This process is called data analytics and refers to the analysis of information from a particular domain (Zadeh, Schiller, Duffy, & Williams, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation